Optimization and intelligent decisions - Sakalauskas, Leonidas; Zavadskas, Edmundas Kazimieras (Technological and Economic Development of Economy, 2009)
Editorial “Optimization and intelligent decisions” Technological and Economic Development of Economy, 15(2), p. 189–196 First published online: 21 Oct 2010